Student Response Systems in higher education: A comparative analysis using Wooclap platform in economic courses - Catala Estada, Belén; Muñoz-Higueras , Diego; Sanjuán Belda, Jordi (Journal of Management and Business Education, 2024)
The introduction of technological tools such as student response systems to dynamise classes in higher education has been increasing in recent years, although often without proper monitoring of their effects. This research aims to analyse the main added value of the use of the Wooclap platform in university education, and whether there are differences in its results depending on the heterogeneous characteristics of the courses and groups in which it is applied. To this end, a comparative analysis has been carried out in three different courses in the field of economics at the University of Valencia. In all three courses, questions were introduced in Wooclap during theory classes. Students in the three courses were given an anonymous survey at the end of the course to evaluate the use of this tool. The students were very satisfied with the tool, highlighting that it helps them to maintain their attention, identify the most important concepts, understand and consolidate them. Furthermore, by means of the Chi-square test, no significant differences were observed in the three groups, from which it can be deduced that beyond the specific characteristics of the course, the profile of the students or the lecturer, this tool can be extrapolated to different contexts and satisfactory results can be expected. The ease of implementation, the possibility of obtaining immediate feedback from students and breaking the monotony of classes are other advantages for lecturers. The conclusions drawn highlight the potential of Wooclap to extend its use in higher education.